KINERJA PEGAWAI BAGIAN UMUM DAN PROTOKOL DI SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Widya Anggraeni; Masjaya .; Adam Idris (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This Research discuss about capability employee of General and Protocol Section in Sekretariat Territory of Kutai Timur Regency. The Problem of Study in this research is how is the capability employee of General and Protocol Section in Sekretariat of Kutai Timur Regency and The factors which are influence capability employee of General and Protocol Section in Sekretariat of Kutai Timur Regency. In order to running the job and wide up responsibility employee of general and protocol section in Sekretariat of Kutai Timur Regency has become challenge to every employee. In running the job the employee must have adaptation with the situation that make employee must to do something which is has not done before. The result of work can be see in duration and effectivity, until now the tasks can be finished well, but sometime there is some minus because in working there is an obstacle unestimate before that make employee difficulity in order to do something which is have not done yet.